Dichotomy of short and long thymic stromal lymphopoietin isoforms in inflammatory disorders of the bowel and skin - Fornasa, Giulia (J Allergy Clin Immunol, 2015)
BACKGROUND: Thymic stromal lymphopoietin (TSLP) is a cytokine with pleiotropic functions in the immune system. It has been associated with allergic reactions in the skin and lungs but also homeostatic tolerogenic responses in the thymus and gut. OBJECTIVE: In human subjects TSLP is present in 2 isoforms, short and long. Here we wanted to investigate the differential expression of the TSLP isoforms and discern their biological implications under homeostatic or inflammatory conditions. METHODS: We evaluated the expression of TSLPs in tissues from healthy subjects, patients with ulcerative colitis, patients with celiac disease, and patients with atopic dermatitis and on epithelial cells and keratinocytes under steady-state conditions or after stimulation. We then tested the immune activity of TSLP isoforms both in vitro and in vivo. RESULTS: We showed that TSLP isoforms are responsible for 2 opposite immune functions. The short isoform is expressed under steady-state conditions and exerts anti-inflammatory activities by affecting the capacity of PBMCs and dendritic cells to produce inflammatory cytokines. Moreover, the short isoform TSLP ameliorates experimental colitis in mice and prevents endotoxin shock. The long isoform of TSLP is proinflammatory and is only expressed during inflammation. The isoforms are differentially regulated by pathogenic bacteria, such as Salmonella species and adhesive-invasive Escherichia coli. CONCLUSIONS: We have solved the dilemma of TSLP being both homeostatic and inflammatory. The TSLP isoform ratio is altered during several inflammatory disorders, with strong implications in disease treatment and prevention. Indeed, targeting of the long isoform of TSLP at the C-terminal portion, which is common to both isoforms, might lead to unwanted side effects caused by neutralization of the homeostatic short isoform.